The Role Of Mass Media In Creating Awareness On Female Sexual Assault - Deepa, J (International Journal of Computer Sciences and Engineering, 2018)
The research paper analyses the sexual violence against women in Tamil Nadu. India seemed to display a contradictory picture with on the one hand, a fast growing economy and progressive indicators of development, but on the other hand portrayed as a country with increasing reports on sexual violence against women and problems with gender inequality. The objective of this study was to try to gain a deeper understanding and reflect upon underlying factors of increased reporting of sexual violence in India especially in Tamil Nadu, and to understand in what way the modernization process possibly could be put in relation to the increased reporting of sexual violence, something that was analysed with help from Durkheim’s theory of anomie. The analysis above suggests that, far from contributing to the discussion and understanding on the structural conditions of violence against women and girls, traditional and new media normalise it. By doing so, media promote genderbased violence. This is why media are currently part of the problem rather than the solution to stopping violence against women. The growth of gender-based violence shows its mechanisms are more sophisticated than they were in the past, as are the forms of representing it in media content. There is a large negotiation across the world that offence against women is frequently failed to report. The report says for every twenty minutes, a woman undergoes sexual assault. There is also a belief that the reported crime data against women is twisted. According to Tamil Nadu police, the consciousness in the midst of women has improved that they confront to file complaints.